CONTROL, PREVENTION AND REPRESSION AGAINST MONEY LAUNDERING IN PERU - Ramón Ruffner, Jeri Gloria (2011)
The article is developed at this time seeking to develop dynamically and extends the theme of control, prevention and suppression of money laundering in Peru: it can also determine their effects on national economic and financial crisis. This project will evaluate three perspectives from the field of International Legal Framework and National Crime money laundering and related offenses, and treatment under Peruvian law and comparative law. It also interpreted the law that established the requirement for audited financial institutions to implement prevention mechanisms, oriented to avoid channeling funds of illicit origin through its operations and its commitment to the Financial Supervisory Authority as supervisor of the State, verify the functionality, appropriateness and effectiveness of these mechanisms. The article not only seeks to highlight the current regulation of laundering money or assets in Peru, but also demonstrate significant technical defects of legislative and policy approach, leading to propose some measures for better performance to the application of notable omissions in Additional provisions relating to parole control. If the assessment and analysis of the results of the investigation determined that these internal control systems of the various regulatory bodies are not capable of understanding the integral control, we propose a model of control system, with their respective implementation methodology that seeks to implement control warning or prevention at different organizational levels to money laundering.